Flos Puerariae-Semen Hoveniae medicinal pair extract ameliorates DSS-induced inflammatory bowel disease through regulating MAPK signaling and modulating gut microbiota composition - Chen, Xiaofan; Zhang, Jiahui; Li, Rui; Zhang, Hua; Sun, Yong; Jiang, Li; Wang, Xiaoya; Xiong, Yaokun (Frontiers in Pharmacology, 2022)
Backgrounds: Inflammatory bowel disease (IBD), a global gastrointestinal disease characterized by relapsing and remitting inflammatory conditions. Flos Puerariae and Semen Hoveniae are traditional Chinese medicine. The medicine pair was used to treat various diseases due to the excellent antioxidative and anti-inflammatory activity, while the effect of extracts from the medicine pair on DSS induced colitis has not been investigated, which hinders the understanding of their mechanisms of action and potential applications. Methods: Accordingly, the chemical constitution of PHE was analyzed by UPLC-LTQ-Orbitrap-MS/MS. The protective effect of PHE on DSS-induced colitis mice was evaluated by body weight loss, disease activity index (DAI) score, colon length shortening, and pathological changes. The levels of inflammatory cytokines were detected by ELISA and RT-qPCR analysis. The oxidative stress (ROS, CAT, SOD, MDA and T-AOC) was analyzed by biochemical kit. The expressions of MAPK were determined by western blotting analysis. The gut microbiota was analyzed by 16S rRNA sequencing. Results: Chemical composition analysis indicated that PHE containing various bioactivities including puerarin, kakkalide, tectoridin, genistin and so on. Findings from this study indicated that PHE effectively modulated histopathological score, inflammatory cell infiltration and inflammatory factor secretion. Noticeably, the oxidative stress was ameliorated by PHE through inhibiting activation of MAPK pathway, leading to decreased inflammatory mediators and restored antioxidative enzymes activity. Furthermore, the composition of gut microbiota was regulated after PHE treatment by improving the abundance of benign bacterial such as Akkermansia and reducing harmful bacterial such as Proteobacteria growth. Conclusion: Findings from this study elucidated the mechanism underlying PHE ameliorated DSS induced intestinal oxidative stress, and the positive impact on restoration of microbiota composition in the gut.